CHEMICAL AND ORGANOLEPTIC PROPERTIES OF COOKIES FROM CORN FLOUR AND MUNG BEAN AS A GLUTEN-FREE SNACKS - Nita Maria Rosiana; Kurnia Cahya Susianti; Arinda Lironika Suryana (Jurnal Pangan dan Agroindustri, 2021)
Autism disorders can reduce the ability to communicate, socialize, and respond to the environment. Some children with autism disorders are allergic to gluten. This study aims to analyze the characteristics of gluten-free cookies from corn flour and mung bean flour. The experimental design used was a Randomized Block Design. The formulation of corn flour : mung bean flour were 60%: 40%, 55%: 45%, 50%: 50%, 45%: 55%, 40%: 60%, each treatment was repeated 5 times. The best treatment is the formulation of 50% corn flour + 50% mung bean flour. The nutrient content of cookies (per 100g) are 18.47 kcal energy, 4.94 grams of protein, 6.93 grams of fat, 25.33 grams of carbohydrates. The serving size for autism children aged 4-6 years is 8 pieces (Â± 80 grams) per day with 2 feeds.